Economic factors in the process of calculation of annuities in bodily injury compensation claims under liability insurance - Jędrzychowska, Anna; Kwiecień, Ilona (Czynniki ekonomiczne w ustalaniu świadczeń rentowych w procesie kompensacji szkód na osobie z ubezpieczeń OC, 2019)
The article constitutes a legal and economic discussion of the economic factors which may and should be taken into account while calculating the benefits compensating the loss of income of the injured and of their families in case of death. The analyzed benefits are an important element of compensation of economic loss in personal injury cases where the compensation is the duty of the perpetrator (or the entity responsible for him/her) within the system based on tort liability. In light of the ubiquitous nature of TPL insurance, the payer is usually the insurance company liable under the granted guarantee. The scope of such cover results from the contract and/or legal acts. The subject calculation was based on an actuarial annuity which also takes into account the likelihood of the claimant and his/ her relatives living until the subsequent periodical payments. The applied calculation is of an illustrative nature with regard to the considerations of the relevant economic assumptions made at the time of loss calculation. The discussion carried out in the article concerns the size and value of the economic factors that can be used in this model.
Financial Sciences. Nauki o Finansach, 2019, vol. 24, no. 1, s. 25-38
Keywords: annuity; compensation; personal demege; time value of money; renta; odszkodowanie; szkody na osobie; wartość pieniądza w czasie